Smart House With Voice Control Lights Using Arduino R3 - Reza Andista Syahputra; Agung Tri Wicaksono (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2025)
Advances in science and technology have improved human life; Now we live in the era of electric voice commands, with a smart home management system that allows people to control home electrical devices such as lights with voice commands, so they don’t have to move to turn off or turn on the lights. When the sound wave user turns on the light or runs the system, the FC-04 sound sensor sends a signal to the microcontroller. The microcontroller then processes the signal into voltage to turn on the light. The FC-04 sound sensor can only produce a digital signal with a value of 1 and 0, which can be collected to the Arduino through the uploaded software to be used as a 5-volt input to turn the lights on or off. Many things can affect the lights when turned on from a certain distance such as the sensitivity of the sound sensor and the noise level around the lights. This research employs an experimental method by designing and testing a system based on the FC-04 sound sensor and Arduino. Testing was conducted to evaluate the sensor's sensitivity, the impact of noise, and the system's accuracy under various conditions. The findings are expected to enhance the efficiency of smart home technology.